BCG lowers plasma cholesterol levels and delays atherosclerotic lesion progression in mice. (August 2016) - van Dam, Andrea D.; Bekkering, Siroon; Crasborn, Malou; van Beek, Lianne; van den Berg, Susan M.; Vrieling, Frank; Joosten, Simone A.; van Harmelen, Vanessa; de Winther, Menno P.J.; Lütjohann, Dieter; Lutgens, Esther; Boon, Mariëtte R.; et al.
Abstract: Background and aims: Bacille-Calmette-Guérin (BCG), prepared from attenuated live Mycobacterium bovis, modulates atherosclerosis development as currently explained by immunomodulatory mechanisms. However, whether BCG is pro- or anti-atherogenic remains inconclusive as the effect of BCG on cholesterol metabolism, the main driver of atherosclerosis development, has remained underexposed in previous studies. Therefore, we aimed to elucidate the effect of BCG on cholesterol metabolism in addition to inflammation and atherosclerosis development in APOE*3-Leiden.CETP mice, a well-established model of human-like lipoprotein metabolism. Methods: Hyperlipidemic APOE*3-Leiden.CETP mice were fed a Western-type diet containing 0.1% cholesterol and were terminated 6 weeks after a single intravenous injection with BCG (0.75 mg; 5 × 10 6 CFU). Results: BCG-treated mice exhibited hepatic mycobacterial infection and hepatomegaly. The enlarged liver (+53%, p = 0.001) coincided with severe immune cell infiltration and a higher cholesterol content (+31%, p = 0.03). Moreover, BCG reduced plasma total cholesterol levels (−34%, p = 0.003), which was confined to reduced nonHDL-cholesterol levels (−36%, p = 0.002). This was due to accelerated plasma clearance of cholesterol from intravenously injected [ 14 C]cholesteryl oleate-labelled VLDL-like particles (t½ −41%, p = 0.002) as a result of elevated hepatic uptake (+25%, p = 0.05) as well as reduced intestinal cholestanol and plant sterol absorption (up to −37%, p = 0.003). Ultimately, BCG decreased foam cell formation of peritoneal macrophages (−18%, p = 0.02) and delayed atherosclerotic lesion progression in the aortic root of the heart. BCG tended to decrease atherosclerotic lesion area (−59%, p = 0.08) and reduced lesion severity. Conclusions: BCG reduces plasma nonHDL-cholesterol levels and delays atherosclerotic lesion formation in hyperlipidemic mice. Highlights: BCG induces mycobacterial infection in hyperlipidemic mice. BCG induces hepatic inflammation and immune activation. BCG lowers plasma cholesterol. BCG delays atherosclerotic lesion progression.